2010
DOI: 10.4028/www.scientific.net/kem.443.645
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Abrasive Jet Micro-Grooving of Quartz Crystals

Abstract: Owing to its various distinct advantages over the other machining technologies, abrasive jet machining has become a promising machining technology for brittle and hard-to-machine materials. An experimental study is presented on the micro-grooving of quartz crystals using an abrasive airjet. The effect of the various process parameters on the major machining performance measures are analysed to provide a deep understanding of this micro-machining process. Predictive models are then developed for quantitatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…However, extreme abrasive flow rate results into inter-particle crashes which reduce the average MRR per particle. The kerf taper angle decreased with growing the abrasive mass flow rate [5]. MRR is increased with increase in mass flow rate of the abrasive [7].…”
Section: Measurement Of the Effect Of Controlling Parameters On Perfomentioning
confidence: 99%
See 1 more Smart Citation
“…However, extreme abrasive flow rate results into inter-particle crashes which reduce the average MRR per particle. The kerf taper angle decreased with growing the abrasive mass flow rate [5]. MRR is increased with increase in mass flow rate of the abrasive [7].…”
Section: Measurement Of the Effect Of Controlling Parameters On Perfomentioning
confidence: 99%
“…As the abrasive jet enters into the work piece, it drops its kinetic energy; therefore, the kerf becomes thinner, and a taper is formed on the kerf. Smaller kerf taper angle observed due to higher air pressure [5]. MRR increased with increase in the air pressure [2,3,4,6,7,11,14,15,16,17,19,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the predicted models provide good results for the range of conditions tested in this study. [14].…”
Section: Fig6-abrasive Jet Machined Profilementioning
confidence: 99%
“…However, the high degree of anisotropy, the trigonal symmetry of the quartz crystal and large etch rate hinder its study and use. Recently, a few micromachining processes such as laser beam machining (LBM) [ 14 ], abrasive jet machining (AJM) [ 15 , 16 ] and electrochemical discharge machining (ECDM) [ 17 , 18 , 19 , 20 , 21 ] have been studied for realizing micro-structures on quartz substrate. Though the etching rate is overtly improved with these technologies, it is not suitable for manufacturing complex structures and mass production.…”
Section: Introductionmentioning
confidence: 99%